Derangements in thyroid hormone status in seriously ill patients: does it matter? - Agrawal, Vaibhav; Kshirsagar, Ashok; Patil, Virendra (International Journal of Advances in Medicine, 2019)
Background: Derangements in stress hormone levels i.e. steroids, thyroid hormones is routinely encountered in almost all the seriously ill patients, which have been found to be associated with morbidity and mortality. The present study was planned to assess the thyroid hormone derangements in seriously ill patients, with respect to mortality. Methods: The present study was a retrospective, observational, record-based study done at Krishna Institute of Medical Sciences, Karad, Maharashtra, India. Results: Out of total 170 patients, 108 were females (63.5%) and 62 (36.4%) were males. On age wise analysis, it was found that majority of the patients were in the age group >50 years comprising of 78 (45.8%) patients. Thyroid hormonal status was deranged in 94 patients (55%), out of which 53 (31%) died and 41 patients (24%) were alive. Most common derangement was seen in free T3 (triiodothyronine), with 60% of the patients showing lowered values, 35% showing raised values and 5% showing normal values. T4 (thyroxine) levels were normal in major bulk of the patients. Conclusions: Serum T3 levels should be routinely done in critically ill patients, to detect any thyroid disorders, which might go undetected until it is too late.